PENTINGNYA ETIKA DALAM PERGAULAN SISWA SEKOLAH DASAR DENGAN METODE DISKUSI DI DESA AIR RUPIK - Mohammad Dani Pratama; Rina Oktaviana (Jurnal Inovasi Penelitian, 2023)
Humans since birth in the world have received education until he entered school. The word education is no longer foreign to our ears, especially education in elementary schools. According to Prof. H. Mahmud Yunus. The definition of education is an effort that is deliberately chosen to influence and help children who aim to improve knowledge, physical and morals so that they can slowly lead children to their highest goals and aspirations. In order for life to be happy and what it does can benefit itself, society, nation, state and religion. As children get older, there are visible cognitive and physical changes in them. Jean Piaget's theory of cognitive development or Piaget's theory shows that intelligence changes as children grow. A child's cognitive development is not only about acquiring knowledge, children must also develop or build mentally